OPTIMALISASI PENERAPAN SISTEM PERWAKAFAN UNTUK PENINGKATAN KESEJAHTERAAN UMAT (STUDI TENTANG SISTEM PENGELOLAAN WAKAF PADA YAYASAN WAKAF UNIVERSITAS MUSLIM INDONESIA MAKASSAR) - A. Jusran Kasim (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
AbstractThis research discusses the optimizing of wakaf management system implementation at the Wakaf Foundation of Indonesian Muslim University (UMI) Makassar with a research focus on how the activity of wakaf fundraising and endowments, the development of wakaf assets, as well as the interpretation of compliance with the Law No. 41 of 2004 on the management of wakaf at Wakaf Foundation of UMI Makassar. The results show that the fundraising and endowments that occurred in the Wakaf Foundation of UMI Makassar are similar to the cash wakaf fundraisingsystem, which in its implementation is still within the foundation's internal domain and has not touched the external one yet. The management of wakaf atthe Wakaf Foundation of UMI Makassar is also not fully in accordance with the Law of the Republic of Indonesia Number 41 of 2004 on wakaf since it lacks of cooperation with the Islamic Financial Institutions (LKS) in terms of the collection and management of wakaf, also lacks of cooperation with theRegistrarOfficials of Wakaf Statement (PPAIW) in the creation of wakaf statement certificate. Nevertheless, the researcher appreciates the Wakaf Foundation of UMI Makassar which has optimized its wakaf fund/asset although it is still within the internal scope of the foundation.